Disseminated tuberculosis following liver transplant presenting with an axillary abscess. (7th February 2014) - Ladds, Emma
Abstract : Four years after an orthoptic liver transplant for hepatocellular carcinoma secondary to alcoholic liver disease, the patient presented in a crescendo manner with skin infections and finally a septic right arm wound. The abscess was drained and cultures grew Mycobacterium tuberculosis . The patient reported a previous episode of 'pneumonia' and subsequent hospitalisations for recurrent chest infections, and following further investigation, he was diagnosed with disseminated tuberculosis. The infection responded to triple therapy, but primary closure of the arm wound was unsuccessful and it was treated conservatively with negative pressure wound therapy. The patient remains an inpatient 3 months after his presentation, responding well to therapy and anticipating imminent discharge. The patient's case serves as a reminder that infections are common in solid organ transplant recipients and clinicians should be aware of unusual or recurrent presentations in these patients, to allow for early diagnosis and timely management.